Electrokinetic sedimentation: a review - Alam, Md. Monjurul; Alam, Md Zahangir; Mohd. Salleh, Hamzah; Tanaka, Takanori; Amosa, Mutiu Kolade; Iwata, Masashi; Jami, Mohammed Saedi (Inderscience Enterprises Ltd., 2016)
Electric field-assisted sedimentation, also called electrokinetic or electroforced sedimentation, is a technology in which electrokinetic effects are utilised to realise an improved solid-liquid separation. Electrokinetic sedimentation practical industrial applications have been limited to the areas such as soil mechanics, civil engineering and the ceramics industry. The aim of this paper is to provide an outline of engineering applications for electrokinetic sedimentation with a focus on the theoretical analysis of electrokinetic sedimentation. In addition, various empirical research results addressing the effects of process parameters on the electrokinetic sedimentation are reviewed. It is hoped that this review would provide relevant information to contemporary researchers who are active in the field of various solid-liquid separation in general and electrokineticsedimentation in particular.